2011
DOI: 10.1021/jp200842u
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles Tethered to Gold Surfaces Using Nitroxyl Radicals

Abstract: We describe the interaction of Au with >NO radicals-the basis of a new method of binding gold nanoparticles to gold substrates. In the sandwich-like system, the gold electrode is separated from the gold nanoparticle layer by thiolated TEMPO radicals. The formation of the NOÀAu bond was confirmed by FAR IR spectroscopy. The properties of the Au substrateÀAu nanoparticle assembly were studied by cyclic voltammetry and scanning tunneling microscopy. Binding of nanoparticles by means of nitroxyl radicals instead o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Our group has recently demonstrated that the nitroxide radicals can be successfully attached to the gold surface by means of Au-O bounds. 46 It seems highly probable that the 5 silver atoms may also form similar bonds with nitroxide radicals. However, it is worth noting that the formation of Ag-O bonds on AgNPs surface must result in a lower coverage of silver surface in comparison with only thiolate-capped AgNPs due to the steric effects associated with the presence of inversely orientated 10 ligands (see structure (2) in Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Our group has recently demonstrated that the nitroxide radicals can be successfully attached to the gold surface by means of Au-O bounds. 46 It seems highly probable that the 5 silver atoms may also form similar bonds with nitroxide radicals. However, it is worth noting that the formation of Ag-O bonds on AgNPs surface must result in a lower coverage of silver surface in comparison with only thiolate-capped AgNPs due to the steric effects associated with the presence of inversely orientated 10 ligands (see structure (2) in Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Nitroxides have been demonstrated to preferentially adsorb to AuNPs upon exchange with the weaker citrate ligand, and the spin-spin exchange interaction between the radical’s unpaired electron and the conduction-band electrons of the AuNPs proposed to mediate this binding. 2527 We used the AuNP’s localized surface plasmon resonance (LSPR) as a sensitive tool 28 to track particle-particle proximity by using UV-vis spectroscopy. 29,30 Nitroxide labelled oligomers can be treated as bivalent ligands that can either promote AuNPs aggregation or stabilize individual particles.…”
mentioning
confidence: 99%
“…Such interactions cause accumulation of the nanoparticles in partially ordered structures but importantly do not lead to the aggregation. Recently our group reported the existence of the interactions of nitroxide radicals with silver and gold nanoparticles/surfaces [ 24 , 26 , 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%